1993
DOI: 10.2307/4088414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Protein Nutritional Status and Immunocompetence in Northern Bobwhite Chicks

Abstract: ABSTR•Cr.-We investigated the effects of dietary protein quality on the development and functioning of the immune system in four-week-old Northern Bobwhite (Colinus virginianus) chicks. Chicks were fed isocaloric diets containing 8, 15, or 33% protein over a three-week period. Significant reductions in the rate of body growth were evident in chicks receiving 8 and 15% protein. Development of the bursa of Fabricius and spleen was significantly depressed in the 8% protein group compared to the other two treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
308
5
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(325 citation statements)
references
References 26 publications
11
308
5
1
Order By: Relevance
“…Parasite-imposed fitness costs are also studied in relation to host life-history trade-offs, such as those between current reproduction and future reproduction or survival (Forbes, 1993 ;Perrin, Christe and Richner, 1996 ;Richner and Tripet, 1999). Given their underlying importance in relation to most of the above-mentioned topics, host immune defences received increasing attention and by the mid-nineties, there were enough research groups measuring and manipulating body condition and immune responses in natural host-parasite associations (Lochmiller, Vestey and Boren, 1993 ;Moller and Saino, 1994 ;Deerenberg et al 1997) to warrant a review on that emerging discipline. ' Ecological Immunology : costly parasite defenses and trade-offs in Evolutionary Ecology ' (Sheldon and Verhulst, 1996) focuses almost entirely on vertebrate hostparasite associations with the exception of a single study on bumble bees (Konig and Schmid-Hempel, 1995).…”
Section: E V O L U T I O N a R Y E C O L O G Y I N T H E L A T E 1980mentioning
confidence: 99%
“…Parasite-imposed fitness costs are also studied in relation to host life-history trade-offs, such as those between current reproduction and future reproduction or survival (Forbes, 1993 ;Perrin, Christe and Richner, 1996 ;Richner and Tripet, 1999). Given their underlying importance in relation to most of the above-mentioned topics, host immune defences received increasing attention and by the mid-nineties, there were enough research groups measuring and manipulating body condition and immune responses in natural host-parasite associations (Lochmiller, Vestey and Boren, 1993 ;Moller and Saino, 1994 ;Deerenberg et al 1997) to warrant a review on that emerging discipline. ' Ecological Immunology : costly parasite defenses and trade-offs in Evolutionary Ecology ' (Sheldon and Verhulst, 1996) focuses almost entirely on vertebrate hostparasite associations with the exception of a single study on bumble bees (Konig and Schmid-Hempel, 1995).…”
Section: E V O L U T I O N a R Y E C O L O G Y I N T H E L A T E 1980mentioning
confidence: 99%
“…Cell-mediated immunity is particularly a¡ected by nutritional condition. Captive northern bobwhite (Colinus virginianus) chicks showed reduced cell-mediated immunity when raised on a low-protein diet, while their humoral immune response (to sheep red blood cells) was not signi¢cantly a¡ected (Lochmiller et al 1993). In addition, there is, to our knowledge, only a single bird study which has experimentally shown the e¡ect of diet quality on immune function under natural conditions.…”
Section: (B) E¡ect Of £Ea Infestation On Cell-mediated Immunitymentioning
confidence: 99%
“…cellmediated immunity, as re£ected in cutaneous hypersensitivity responses to an injection of phytohaemagglutinin (PHA; Lochmiller et al 1993;Roitt et al 1996;Saino et al 1997a). Such an analysis might indicate whether ectoparasite infestation potentially alters the host's susceptibility to other pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…As the maturation of immune function may take up to several weeks after hatching (Klasing & Leshchinsky 1999), rearing conditions experienced by nestlings at this time may substantially affect the development of immunity. Indeed, poor nutrition during growth has been demonstrated to slow the development of the immune system through impaired growth of lymphoid organs and suppressed humoral and cellular immune responses (Lochmiller et al 1993;Birkhead et al 1999;Hoi-Leitner et al 2001). Recent studies have shown that nestlings from naturally large or experimentally enlarged broods, presumably thereby experiencing poor rearing conditions, have lower T-cell-mediated immune responses than nestlings from small or experimentally reduced broods (Saino et al 1997;Hõ rak et al 1999).…”
Section: Introductionmentioning
confidence: 99%